1999
DOI: 10.1001/archpedi.153.10.1098
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Incomplete Carbohydrate Absorption From Fruit Juice Consumption in Infants

Abstract: Background: Most infants consume fruit juices by 6 months of age. However, fruit juices containing sorbitol may be associated with carbohydrate malabsorption without clinical symptoms. We hypothesized that increased physical activity and metabolic rate may be associated with carbohydrate malabsorption. Methods: Physical activity and metabolic rate were determined in 14 healthy infants ([mean ± SD] age, 5.1 ± 0.8 months; weight, 7.8 ± 1.1 kg; length, 67 ± 4.2 cm; and body fat, 26% ± 5%) for 3 hours in a respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 18 publications
(23 reference statements)
1
32
0
Order By: Relevance
“…The breath hydrogen test, which measures bacterial fermentation products of D-glucose, is relatively sensitive and has been used in children to assess bacterial overgrowth and carbohydrate malabsorption (24, 26). The choice of D-glucose rather than lactulose in children with SBS reduces the false-positive rate, because, glucose is rapidly absorbed by the small intestines (27).…”
Section: Discussionmentioning
confidence: 99%
“…The breath hydrogen test, which measures bacterial fermentation products of D-glucose, is relatively sensitive and has been used in children to assess bacterial overgrowth and carbohydrate malabsorption (24, 26). The choice of D-glucose rather than lactulose in children with SBS reduces the false-positive rate, because, glucose is rapidly absorbed by the small intestines (27).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sweetened beverages, including fruit juices, are associated with negative health outcomes due to increase adiposity gain in low-income children [33]. Carbohydrate malabsorption is also high in infants consuming sorbitol-containing juices with high fructose-to-glucose ratio which has a negative impact on metabolism and activity [34]. The American Academy of Pediatrics [35] recommends reducing overall fruit juice intake among children and replacing it with whole fruits due to these documented negative effects associated with intake of large volumes of fruit juices.…”
Section: Discussionmentioning
confidence: 99%
“…Upon completion of the 24-hour metabolic measurement, macronutrient intake was determined from the amount of formula or complementary food fed utilizing the manufacturer's proximate analysis. This methodology of determining nutrient intake is valid and has been utilized in several previous studies in infants [21,22] and adults [20,23]. Investigators also recorded the interaction time and type of interaction and the observed periods of infant sleep.…”
Section: Methodsmentioning
confidence: 99%